Penile replantation - K S Krishnakumar; Kiran S Petkar; Sameer Lateef; Suresh Vyloppilli (Indian Journal of Plastic Surgery)
Penile amputation is rare and hence the paucity of experience and publication. We present our case of self-inflicted penile amputation, which was successfully managed with microsurgical replantation, with relevant literature review.